The relationship between jump performance, speed and COD speed in elite female soccer players - Stankovic, M.; Ðordevic, D.; Aleksic, A.; Lazic, A.; Lilic, A.; Capric, I.; Trajkovic, N. (Facta Universitatis: Series Physical Education and Sport, 2022)
The purpose of this study was to present the physical performance of elite female soccer players and to analyze the relationship between jump performance, speed and COD ability. Sixteen elite female soccer players (age: 20.05±2.85; height: 166.47±4.83cm; body weight: 60.52±8.30kg, BMI 21.88±2.86) from a women's club who played the highest rank of the competition took part in this study. The jump, speed and COD abilities of each player were determined using: (1) the Squat jump (SJ), (2) Countermovement Jump (CMJ), countermovement jump with arm swing (CMJA), (2) running speed at 30-m with passing time at 10m and 20m, (3) the pro agility test (pro), (4) zig-zag test (zig-zag), (5) 9-6-3-6-3 sprint (9-6-3-6-9). The results of Pearson`s correlation indicated moderate significant relationships between the 10m running speed and pro agility test (r=0.59; p<0.01), as well as the zig-zag test (r=0.55; p<0.01), and also between the 30m and all COD tests (pro agility r=0.66; p<0.01, zig-zag r=0.59; p<0.01 and 9-6-3-6-9 r=0.58; p<0.05). A small correlation (r=0.49; p<0.03) was noticed between the 10m running test and 9-6-3-6-9 agility test, and also between the CMJA (r=0.45; p<0.05) and the 9-6-3-6-9 agility test. The findings of the present study indicated a significant correlation between speed and all of the COD tests, additionally between the CMJA and 9-6-3-6-9 COD test. Therefore, elite female soccer players with higher maximum acceleration rates and speed tend to perform better in change of direction tests. On the other hand, jump performance does not significantly correlate with COD ability.